2017
DOI: 10.1016/j.jceh.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Simple Anthropometric Indices are Useful for Predicting Non-alcoholic Fatty Liver Disease [NAFLD] in Asian Indians

Abstract: The simple anthropometric parameters, such as BMI, waist circumference, waist-hip ratio and waist-height ratio are useful for predicting NAFLD in Indian adults. The anthropometry cut offs would be very useful in setting target points of life style modification and weight reduction. Besides, our study also clearly demonstrated that a simple assessment of BMI is as efficacious as other anthropometry parameters in predicting NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Generally, BMI<25 and BMI≥25 indicate normal body weight and obesity, respectively [ 22 ]. Abdominal obesity was considered as WC≥102 cm and WHR≥0.9 in men and WC≥88 cm and WHR≥0.85 in women (WHR = WC/HC) [ 19 ]. A WHtR of ≥0.5 (WHtR = WC/height) permits identifying obesity.. WHtR≥0.5 indicates an increased risk of obesity-related diseases in both genders in all races [ 19 ].…”
Section: Study Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, BMI<25 and BMI≥25 indicate normal body weight and obesity, respectively [ 22 ]. Abdominal obesity was considered as WC≥102 cm and WHR≥0.9 in men and WC≥88 cm and WHR≥0.85 in women (WHR = WC/HC) [ 19 ]. A WHtR of ≥0.5 (WHtR = WC/height) permits identifying obesity.. WHtR≥0.5 indicates an increased risk of obesity-related diseases in both genders in all races [ 19 ].…”
Section: Study Measurementmentioning
confidence: 99%
“…Abdominal obesity was considered as WC≥102 cm and WHR≥0.9 in men and WC≥88 cm and WHR≥0.85 in women (WHR = WC/HC) [ 19 ]. A WHtR of ≥0.5 (WHtR = WC/height) permits identifying obesity.. WHtR≥0.5 indicates an increased risk of obesity-related diseases in both genders in all races [ 19 ]. The WC and WHR were measured using a tape measure with a precision of 0.1 cm at the midpoint of the lower limit of the last rib and above the lower part of the iliac crest in the maximal hip circumference position, respectively.…”
Section: Study Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated that the appropriate cutoffs for BMI in screening for NAFLD were 24 in Chinese [ 30 ], 24.4 in Asian Indian [ 36 ], and 23.2 in Iranian [ 37 ] patients. BMI = 25 was defined as a cutoff for obesity among people in the Asia-Oceania region [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol had gained approval from The Ethics Committee of Widya Mandala Catholic University Surabaya Faculty of Medicine. The ideal waist-to-hip ratio is < 0.9 for males and < 0.85 for females.The high ratio is  0.9 for males and  0.85 for females(17).…”
mentioning
confidence: 93%